SOFTWARE DEVELOPMENT TEAMS. - Sawyer, Steve (Communications of the ACM, 2004)
This article focuses on software development by analyzing the ways software developers organize. By taking this social perspective, the article highlights how software production methods, techniques and tools are enmeshed in and enacted through the structures and interactions of the professionals who work together to build software. A social perspective considers the team as the unit of analysis, seeing it as more than the aggregate of individual software developers' attributes and actions. A social perspective contrasts with production-focused views of software development; social action becomes the focal activity, not the by-product of a method's prescription. More common perspectives on software development, such as the Software Engineering Institute's Capability Maturity Model (CMM), focus on the means of production — a techno-social approach. The People-Capability Maturity Model (P-CMM) complements this by explaining how people can best change their behavior to fit the CMM approach. Together, the CMM and PCMM reflect the traditional production first, people second, approach. INSET: Conceptual Bases of the Three Archetypes.